Variant ATRX Syndrome with Dysfunction of ATRX and MAGT1 Genes. Issue 1 (10th November 2013) - Qiao, Ying; Mondal, Kajari; Trapani, Valentina; Wen, Jiadi; Carpenter, Gillian; Wildin, Robert; Price, E. Magda; Gibbons, Richard J.; Eichmeyer, Jennifer; Jiang, Ruby; DuPont, Barbara; Martell, Sally; et al.
<x xml:space="preserve">Abstract</x> A 0.8kb intronic duplication in MAGT1 and a single base pair deletion in the last exon of ATRX were identified in a family with 5 males demonstrating intellectual disability (ID) and unusual skin findings. Dysfunction of MAGT1 and ATRX was detected using a panel of tests and indicates the role of ATRX mutation in ID and MAGT1 disruption in abnormal skin findings. This work emphasizes the importance of correlating clinical phenotype with genomic and cell function analyses to explain the phenotypic variability of syndromic ID. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>